International military operations in the 21st Century global trends and the future of intervention (Routledge/Taylor & Francis Group, 2015)
This book examines the challenges that military forces will face in multinational operations in the 21st century. Expanding on Rupert Smith's The Utility of Force, the volume assesses the changing parameters within which force as a political instrument is ultimately carried out. By analysing nine carefully selected mission types, the volume presents a comprehensive analysis of key trends and trajectories. Building upon this analysis, the contributors break the trends and parameters down into real and potential tasks and mission types in order to identify concrete implications for military forces in future multinational operations. The context of military intervention in conflicts and crises around the world is rapidly evolving. Western powers' shrinking ability and desire to intervene makes it pertinent to analyse how the cost of operations can be reduced and, how they can be executed more intelligently in the future. New challenges to international military operations are arising and this book addresses these challenges by focusing on three key areas of change: 1) An increasingly urbanised world; 2) The changing nature of missions; 3) The commercial availability of new technologies. In answering these questions and embracing some of the insights of a growing field of future studies, the volume presents an innovative perspective on future international military operations. This book will be of much interest to students of international intervention, military and strategic studies, war and conflict studies, security studies and IR in general.